Identifikasi Aren untuk Memetakan Potensi Bahan Baku Gula Semut yang Berkelanjutan di Dusun Gunungsurat, Pekalongan - Nurul Hidayah; Aji Hermawan; Sugeng Heri Suseno; Prayoga Suryadarma; Danang Aria Nugroho (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Gunungsurat is one of the hamlets in Botosari Village, Paninggaran Subdistrict, Pekalongan District. Gunungsurat is located between of hill, so it is very suitable for sugar palm growth. The purpose of identification of sugar palm is done to determine amount of sugar palm that ready to produced, not yet produced, and production of sap to mapping a potency of sugar palm as the raw material for making sugar. Furthermore, to reduce the level of logging of palm trees that are not environmentally friendly. The method that used by surveying farmers and direct observation of the land. Variables that taken from the data include total of sugar palm trees, total of palm trees tapped, estimated tree age, stem height, and production of sap/may/day. The results that obtained are 784 palm trees that grow naturally in Gunungsurat with 92 production age trees and 692 trees not yet produced. The average height of sugar palm is 10 meters with production of ± 10-15 L/may/day. It is expected that this identification can provide information to the public regarding the potential of sugar palm as the raw material for making sugar in Gunungsurat.